IMPLEMENTING PICTURE DICTATION IN IMPROVING SPEAKING ABILITY OF THE SECOND YEAR STUDENTS AT MA PESANTREN GUPPI SAMATA - Kasmi ,; Indah Fadhilah Rahman (Universitas Islam Negeri Alauddin Makassar, 2017)
The objective of this research is to improve speaking ability by Implementing Picture Dictation of the Second Year Students (II B) at MA Pesantren GUPPI Samata Kabupaten Gowa. This research was a Classroom Action Research (CAR). It was conducted in two cycles, which was held three meetings in its every cycle. The subject of this research was the students of eleventh grade of MA Pesantren GUPPI Samata Kabupaten Gowa. They are XI B which consisted of 20 students with 10 boys and 10 girls. The data were quantitative obtained from tests (preliminary study test, first cycle test, and second cycle test) and observation guidelines. The result of this research showed that improvement of the students’ speaking ability from the first cycle to the second cycle has improved. The mean score of vocabulary terms was 3.20 in the first cycle test and became 3.80 in the second cycle test. Besides that, the mean score of grammar in the first cycle was 3.45 became 3.95 in the second cycle. Then, pronunciation terms, the students score from first cycle to the second cycle was 3.20 became 3.65. Furthermore for the students’ speaking accuracy and fluency, their score also increase from 3.40 became 3.70. Based on the data above, the researcher concludes that using picture dictation increased the speaking ability of the Second Year Students (II B) at MA Pesantren GUPPI Samata.